Evaluasi Modulus Resilien dan Perilaku Fatigue Campuran Stone Matrix Asphalt (SMA) Menggunakan Aspal Modifikasi Asbuton Murni Lawele - Khodijah Al Qubro; Murtaza Haider Syed; Ghina Amalia; Iva Nazila; Sri Hendarto; Rio Ramadhan; Miftahul Jannah Lubis (Universitas Batanghari Jambi, 2026)
Pure Lawele Asbuton is a local natural asphalt with a high bitumen content and significant potential as a sustainable alternative binder for road pavement applications. This study aims to evaluate the mechanistic performance of Stone Matrix Asphalt (SMA) mixtures incorporating Lawele Asbuton through resilient modulus and fatigue resistance testing. SMA mixtures containing Lawele Asbuton were compared with mixtures using conventional Pen 60/70 asphalt and polymer-modified asphalt Starbit E-55. All tests were conducted at the Optimum Asphalt Content (OAC) determined using the Marshall method. The results indicate that SMA mixtures with modified binders exhibit superior mechanistic performance compared to Pen 60/70 asphalt. The PMA 2% mixture achieved resilient modulus values of 578 MPa at 35°C and 198 MPa at 45°C, along with a fatigue life of 242,660 cycles at a strain level of ±400 µε, which is significantly higher than that of the Pen 60/70 mixture. These findings demonstrate that pure Lawele Asbuton (PMA 2%) has strong potential as a local alternative binder capable of enhancing the structural performance and fatigue resistance of SMA mixtures.